Producing seed yams (Dioscorea rotundata Poir.) using yam peels - Aighewi, B.A.; Asiedu, Robert; Akoroda, M.O. (2003)
Large quantities of yam (Dioscorea rotundata), up to 30% of harvested tubers is usually reserved as planting material for the next crop. This experiment was conducted to assess the use of yam peels of Abi and Pepa yam varieties of 5-, 10-, 15-, and 30- to 40-mm thickness, for seed yam production. Pepa had poorer crop establishment and produced fewer but larger tubers than Abi